MODERN TEACHING TECHNIQUES IN IMPROVING COGNITIVE SKILLS AMONG SCHOOL CHILDREN –A NOVEL APPROACH - R.V.GEETHA,; V. VISHNU PRIYA, (International Journal of Pharma and Bio Sciences, 2016)
Cognition refers to mental activity including thinking, memory, psycholinguistics, comprehension, motivation, perception and self confidence. When cognitive approach is applied to learning and teaching, focus is on understanding of information and concepts. If we are able to understand the connections between concepts, breakdown information and rebuild with logical connections, then our retention of material and understanding capacity will be improved. To improve the cognitive skills among school children by using modern teaching techniques. The study participants were from a school following uniform curriculum in Chennai. The control group and study group participants were exposed to conventional teaching and novel modern teaching methodology respectively. The results were statistically analysed and found to be statistically significant. This study revealed that modern teaching techniques are one of the effective and efficient method in improving the cognitive skills of the school students to make them perform better in their education.